ECONOMIC FEASIBILITY ANALYSIS OF SAGO PALM DEVELOPMENT IN SUNGAI APIT AND SABAK AUH SUB-DISTRICT, SIAK REGENCY - Dwi Widiarsih (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2019)
Sago is a native Indonesian plant that grows in the Indonesian Archipelago Coastal Zone. In Indonesia the centers of sago plantations are spread in Papua, West Papua, Maluku, North Maluku, Riau, Sulawesi and Kalimantan. Sago can be an alternative to meet food and energy needs. The current development of sago is urgent because the fulfillment of food in Indonesia currently only leads to one commodity, namely rice, while the rice diversification program has not gone well.The development of the plantation sector, especially sago plants in Siak Regency, is part of regional development, which aims to increase the production, income, welfare and prosperity of the community in harmony with regional potential so that the plantation sector, especially sago plants, can play an important role to develop regional economy, support regional development, create job opportunities, encourage the development of downstream industries and support the preservation of natural resources and the environment.The availability of food which is not the main food in Siak Regency, especially the sago plant has an area of 11,557.00 ha with production reaching 19,904.00 tons. In realizing the above role in an effort to increase the production of sago plants, it is necessary to have an economic feasibility study of sago plant development activities in the Sungai Apit and Sabak Auh Sub-district, Siak Regency. Economic feasibility analysis aims to assess whether the development of sago plants is feasible or not economically to be developed in the coastal areas of Sungai Apit and Sabak Auh Sub-district, Siak Regency. The analysis used uses the Payback period method, Return on investment, Net present value, and Internal rate of return